Population estimates and land cover use of wintering Mountain Plovers in Texas - James E. Lyons; Brad Andres; Kelli L. Stone; Allison K Pierce; Kammie Kruse (Journal of Field Ornithology)
Conservation of migratory birds throughout the full annual cycle requires a comprehensive understanding of abundance and distribution in interconnected breeding, migration, and wintering habitats. The Mountain Plover ( Anarhynchus montanus ) is a rare endemic breeder of the Rocky Mountain and Great Plains regions that migrates to wintering grounds in the southwestern USA and northern Mexico. Information regarding its wintering abundance and distribution, particularly in Texas, is limited. This study provides the first population estimate for Mountain Plovers wintering in Texas and examines factors influencing their land cover use. Through distance sampling surveys in six ecoregions of Texas, we estimated an annual wintering population of 3096 (95% CI 1464–6547) Mountain Plovers during 2019–2020, with the greatest abundances in the Southern Texas Plains and Western Gulf Coastal Plain ecoregions. The highest plover densities were in the Southern Texas Plains and Central Great Plains ecoregions. Most plovers were found in cultivated crops, particularly tilled fields and sod farms, and plovers preferentially selected crop fields without residual vegetation or stubble. Grass/hay fields were used less, perhaps because of tall vegetation. Our findings highlight the significance of Texas as a wintering area for Mountain Plovers and emphasize the importance of specific cropland habitats for this species. These results provide crucial insights for conservation and management efforts aimed at protecting Mountain Plovers throughout their annual cycle.